Perancangan Interior Musem Wayang Potehi di Surabaya - Faradila Chandra; Grace Mulyono (Intra, 2014)
The potehi puppet was a culture from Chinese be in the form of hand’s doll which played with colonial story. In the period of reformation, the potehi puppet had no permition from President wheresoever to all Chinese culture can’t show in public. Nowadays Chinese culture can show in public again. But many people had no interest for this culture because they assuming that thing so boring. Surabaya is a East Java’s capital where the potehi puppet came for the first time through market’s route ago so this place will be so compatible if there is a museum of potehi puppet. Hopefully, with this design planning people will have a place to give more acknowledges from one of Chinese culture where they were minority in Indonesia and so ever got discrimination in new orde’s period, knowing Indonesia is “Bhineka Tunggal Ika”.